High Ki67 expression is an independent good prognostic marker in colorectal cancer. Issue 3 (17th August 2015) - Melling, Nathaniel; Kowitz, Charlotte Marie; Simon, Ronald; Bokemeyer, Carsten; Terracciano, Luigi; Sauter, Guido; Izbicki, Jakob Robert; Marx, Andreas Holger
Abstract : Aims: To correlate Ki67 expression with outcome in colorectal cancer (CRC). Methods: Ki67 labelling index (Ki67LI) was analysed by immunohistochemistry on a tissue microarray containing 1800 CRCs. The results were compared with clinicopathological and molecular parameters. Results: Ki67LI was considered low in 26.3%, moderate in 56.7% and high in 17.0% of 1653 interpretable CRCs. High Ki67 expression was associated with low tumour stage (p<0.0001) and nodal status (p=0.0315), but not with tumour grade (p=0.8639), histological tumour type (p=0.1542) or tumour localisation, and was an independent prognosticator of favourable survival (p=0.0121). High Ki67 expression was also significantly associated with high-level nuclear β-catenin and p53 expression (p<0.0001 and p=0.0095, respectively). Conclusions: In summary, our data show that high Ki67 expression in CRCs is associated with good clinical outcome. Ki67, p53 and β-catenin overexpression seem to be linked to CRC, and indicate a cellular state of high proliferative activity. Finally, our findings strongly argue for a clinical utility of Ki67 immunostaining as an independent prognostic biomarker in CRC.